VIOLATION OF THE MAXIM OF POLITINESS IN LANGUAGE ON A MEME CONTAINING THE PRESIDENTIAL CANDIDATE OF THE REPUBLIC OF INDONESIA PERIOD 2024-2029 - Miftahulkhairah Anwar; Fachrur Razi Amir; Muhammad Bagas Ilhami; Moh. Arief Rakhman (Adisam Publisher, 2024)
The role of language is very important in campaigns because language is able to mobilize the masses and influence people's behavior. Ideally, campaigns present persuasive language that contains honest and polite information. However, the phenomena in the field are different from those idealized. This paper will describe the phenomenon of violations of language politeness maxims in presidential election memes. The method used is a qualitative descriptive method. The data in this research was collected from documentation in the form of meme images on the internet, focusing on the three presidential candidates announced by the General Election Commission (KPU). The three presidential candidates are Anies Baswedan, Prabowo Subianto, and Ganjar Pranowo. As a result, the language character in meme media containing presidential candidates is colored by language impoliteness. This linguistic impoliteness takes the form of violations of the language politeness maxim as follows: 27% violation of the approbation maxim, 12% violation of the opinion reticence maxim, 13% violation of the agreement maxim, modesty maxim) by 5%, violation of tact maxim by 25%, violation of the feeling reticence maxim by 13%, violation of the generosity maxim by 4%, and violation of the sympathy maxim of 1%. This violation has the potential to trigger conflict between supporters. Therefore, to create peaceful elections, memes should not contain any forms of politeness violations.